Analytical and numerical models for thermal related design of a new pico-satellite. (August 2019) - Bonnici, Mario; Mollicone, Pierluigi; Fenech, Maurizio; Azzopardi, Marc Anthony
Highlights: Thermal response prediction of a pico-satellite is critical. A thermal modeling tool was developed and applied to a custom design pico-satellite. Two independent modelling techniques were used and the two models agreed. Maximum temperatures can be controlled by adjusting thermal surface finish. Minimum temperatures are harder to control. Abstract: Modelling, simulating and testing the on-orbit thermal behaviour of a pico-satellite before launch is critical to ensure component reliability and performance. Due to small thermal inertia and hence small time constant, a pico-satellite may undergo larger temperature swings than those experienced by larger satellites. Weight, size and power limitations are especially restrictive in pico-satellites and limit thermal control to passive systems such as controlling conduction and radiation heat transfer paths. A lumped parameter thermal model was developed to study the on-orbit thermal response of the UoMBSat-1 PocketQube, Malta's first pico-satellite project. A numerical finite element model is presented in order to test and validate the thermal model and passive thermal control. Small satellites are usually launched on rockets as piggyback satellites; therefore, orbit parameters are rarely known in the early stages of the project and various launch opportunities would need to be evaluated and compared. This paper presents a parametric analysis where the effects of orbit parameters, such as altitude and beta angle, on the thermal response are evaluated. We show that by controlling the surface finish and beta angle, it is possible to place a pico-satellite in a thermal regime that is suitable for typical electronic components, and batteries.